A bifunctional triphenylamine-based electrochromic polymer with excellent self-healing performance. (1st October 2018) - Zheng, Rongzong; Fan, Yaru; Wang, Yi; Wan, Zhongquan; Jia, Chunyang; Weng, Xiaolong; Xie, Jianliang; Deng, Longjiang
Abstract: The cracking of electrochromic materials due to aging or reiterative bending is a major problem which noticeably degrades the performances of electrochromic devices. In this research, a novel self-healing electrochromic polymer PPFMA was synthesized, which integrated the electrochromic triphenylamine unit and self-healing Diels-Alder group. The PPFMA film shows all superior electrochromic properties, such as stable color changes (yellow to green to blue) with a maximum optical contrast of 42.7% at 1050 nm and high coloration efficiency of 108.3 cm 2 C -1 . Meanwhile, the polymer PPFMA film also shows excellent self-healing performance, cracks on the film surfaces (bleached or colored states) could be self-healed at 110 °C within 4 min, and the self-healing rate is about 80%. The results indicate that polymer PPFMA has the mutual independent bifunction of electrochromic and self-healing, it is a promising material to solve the problem of cracks generation for the electrochromic device. Graphical abstract: Image 1